A Systematic Review of Overweight, Obesity, and Type 2 Diabetes Among Asian American Subgroups - Staimez, Lisa R.; Weber, Mary B.; Narayan, K. M. Venkat; Oza-Frank, Reena (Current Diabetes Reviews, 2013)
This systematic review synthesizes data published between 1988 and 2009 on mean BMI and prevalence of overweight, obesity, and type 2 diabetes among Asian subgroups in the U.S. We conducted systematic searches in Pub- Med for peer-reviewed, English-language citations that reported mean BMI and percent overweight, obesity, and diabetes among South Asians/Asian Indians, Chinese, Filipinos, Koreans, and Vietnamese. We identified 647 database citations and 23 additional citations from hand-searching. After screening titles, abstracts, and full-text publications, 97 citations remained. None were published between 1988 and 1992, 28 between 1993 and 2003, and 69 between 2004 and 2009. Publications were identified for the following Asian subgroups: South Asian (n=8), Asian Indian (n=20), Chinese (n=44), Filipino (n=22), Korean (n= 8), and Vietnamese (n=3). The observed sample sizes ranged from 32 to 4245 subjects with mean ages from 24 to 78 years. Among samples of men and women, the lowest reported mean BMI was in South Asians (22.1 kg/m2), and the highest was in Filipinos (26.8 kg/m2). Estimates for overweight (12.8 - 46.7%) and obesity (2.1 – 59.0%) were variable. Among men and women, the highest rate of diabetes was reported in Asian Indians with BMI ≥ 30 kg/m2 (32.9%, age and sex standardized). This review suggests heterogeneity among U.S. Asian populations in cardiometabolic risk factors, yet comparisons are limited due to variability in study populations, methods, and definitions used in published reports. Future efforts should adopt standardized methods to understand overweight, obesity and diabetes in this growing U.S. ethnic population.
Keywords: Ethnicity